Citotoxicidad de Hidroxiapatita y su morfología en composites con Ti - Comin, Romina (2013)
Hydroxyapatite (Ca10(PO4)6(OH)2 is the material used to improve osseointegration of implants in humans. Traditionally Ti-based implant is coated with hydroxyapatite, but this presents several problems such as, low fracture toughness of hydroxyapatite, generation of interfacial cracks during the deposition step and low adhesion ceramic /metal. Furthermore some studies reported that some excellent Ti-HA bio-composites could be fabricated by the powder metallurgy (PM) technology. In present study it was investigate the cytotoxicity of coralline and bovine hydroxyapatite. Topography of Ti-HA composites obtained by powder metallurgy was evaluated by scanning electron microscopy. The results showed that HA samples analyzed did not affect cell viability. Furthermore, a good integration of HA to the matrix of Ti was observed by microscopy studies